Cardiovascular reflex - Jenie, Ikhlas Muhammad (Universitas Muhammadiyah Yogyakarta, 2007)
It is familiar to measure cardiovascular parameters, such as blood pressure and pulse rate, in health care practice. The importance of such measure in clinical practice is out of question. Those cardiovascular parameters, basically, are products of reflex. In this paper, we would like to describe the basic tenets of cardiovascular reflex limited to that governed by autonomic nervous system, but not to that exerted by mechanical and local factors. The cardiovascular reflexes to be discussed are arterial baroreflex, cardiopulmonary baroreflex, cardiovascular reflex of stimulation of peripheral chemoreceptors, cardiovascular reflex associated to stimulation of exteroceptors, and interaction among those reflexes.